Peran Wardrobe Dan Make Up Dalam Persiapan Syuting Film Sabda Rindu - Bila, Salsa; Edlina, Ria (Jurnal Ilmu Komunikasi Dan Media Sosial (JKOMDIS), 2024)
This final assignment report was prepared based on the author's experience during the film making project entitled "Sabda Rindu". The production of the film Sabda Miss took approximately 3 months, during which the writer received a job desk as wardrobe and make up. According to Umbara (2001: 143), a wardrobe in the true sense is a wall cupboard where clothes are stored. In the film, the term wardrobe is directly interpreted as everything that the actors wear, whether in the form of clothes or accessories attached to their bodies. Wadrobe in a film functions as one of the ways used to communicate between characters and the audience. When creating a wardrobe, fashion stylists have to consider the choice of colors to be used in the wardrobe. Visual color has its own language that is able to convey the mood of the characters in a film. Choosing the right color can be a form of supporting character through interpreting the meaning of color. The film Sabda Rindu is an Indonesian film by Dharma Andalas students of the Communication Science Study Program with the Slice Of Life genre. The film Sabda Rindu tells the story of a child who suffers from cancer and his parents who are separated. So the child has to live separately from his parents, and the child has to fight his illness by living in an orphanage, with other cancer sufferers. The theories used are interpersonal communication theory and symbolic communication.